Numerical analysis on the effects of cavity geometry with heat towards contaminant removal - Asril Saadun, Mohd. Noor (2012)
These studies present a computational investigation of fluid-solid interaction flow in a channel. Fluid-solid interaction flow was created in three different shapes of cavity with additional constant heat flux under the floor of a horizontal channel. The flow and solid particle dynamics were explored using Cubic Interpolated Pseudo-Particle (CIP) method and Lagrangian scheme of Newton's law respectively for two main objectives. The first is to demonstrate the validity of the proposed Eulerian-Lagrangian in predicting the main characteristics of fluid-solid interaction flow. The second objective is to shed the light on the dynamics of the solid particle that take place in three types of cavities with heat effect, which has not been fully covered in the literature before. The results show that the particles trajectories are critically dependent on the magnitude of Reynolds numbers and the vortex behavior in the cavity and also buoyancy effect. Good comparisons with the previous studies demonstrate the multidisciplinary applications of this scheme.